Language, intellectual and educational outcomes after moderate-to-severe traumatic brain injury sustained before the age of 18 months. (3rd July 2019) - Vassel-Hitier, Jeanne; Verdier, Valentine; Rasquier, Stéphanie; Chalard, Anaïs; Laurent-Vannier, Anne; Chevignard, Mathilde
ABSTRACT: Objective : The aim of this study was to assess long-term outcomes in terms of oral language, intellectual ability, education, following very early moderate-to-severe TBI. Methods : Children who had been hospitalized in rehabilitation after moderate-to-severe TBI sustained before 18 months of age were contacted once they had reached school age. Detailed oral language and intellectual ability assessment were performed, and information on ongoing education was collected. Results : 52 children met inclusion criteria; 21 (40.4%) participated [13 males, mean age 7.5 years (SD = 1.9), age at injury 0.7 years (SD = 0.5), time since injury 6.8 years (SD = 1.8)]. Performance was in the clinical range (<-2SD) for: syntactic comprehension (67%; mean z-scores −2.6; SD = 3.1), syntactic expression (62%; −2.1; SD = 1.3), lexical stock extent (57%; −1.5; SD = 1.5), lexical access skills (48%; −1.9; SD = 2), and semantic organization (32%; −0.9; SD = 1.2). Full-scale IQ was <90 for 91%. Only eight children followed mainstream education without adaptations. Performance on all language tests (except lexical stock extent) was significantly poorer for children with a personal school aid or those in specialized education. Conclusions : Early moderate-to-severe TBI causes significant delayed language (especially syntactic aspects of language) and cognitive disabilities, with consequences on long-term educational outcome. These children require long-term follow-up and timely interventions.